Mind and cosmos why the materialist neo-Darwinian conception of nature is almost certainly false - Nagel, Thomas, 1937- (New York ; Oxford : Oxford University Press, 2012)
Thomas Nagel argues that the widely accepted world view of materialist naturalism is untenable. The mind-body problem cannot be confined to the relation between animal minds and animal bodies. If materialism cannot accommodate consciousness and other mind-related aspects of reality, then we must abandon a purely materialist understanding of nature in general, extending to biology, evolutionary theory, and cosmology.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Cosmology; Cosmogony; Science -- Philosophy; Darwin, Charles, -- 1809-1882.